Sensory Arsenal on the Stinger of the Parasitoid Jewel Wasp and Its Possible Role in Identifying Cockroach Brains - Gal, Ram; Kaiser, Maayan; Haspel, Gal; Libersat, Frederic (PLOS ONE, 2014)
The parasitoid jewel wasp uses cockroaches as live food supply for its developing larva. To this end, the adult wasp stings a cockroach and injects venom directly inside its brain, turning the prey into a submissive ‘zombie’. Here, we characterize the sensory arsenal on the wasp’s stinger that enables the wasp to identify the brain target inside the cockroach’s head. An electron microscopy study of the stinger reveals (a) cuticular depressions innervated by a single mechanosensory neuron, which are presumably campaniform sensilla; and (b) dome-shaped structures innervated by a single mechanosensory neuron and 4–5 chemosensory neurons, which are presumably contact-chemoreceptive sensilla. Extracellular electrophysiological recordings from stinger afferents show increased firing rate in response to mechanical stimulation with agarose. This response is direction-selective and depends upon the concentration (density) of the agarose, such that the most robust response is evoked when the stinger is stimulated in the distal-to-proximal direction (concomitant with the penetration during the natural stinging behavior) and penetrating into relatively hard (0.75%–2.5%) agarose pellets. Accordingly, wasps demonstrate a normal stinging behavior when presented with cockroaches in which the brain was replaced with a hard (2.5%) agarose pellet. Conversely, wasps demonstrate a prolonged stinging behavior when the cockroach brain was either removed or replaced by a soft (0.5%) agarose pellet, or when stinger sensory organs were ablated prior to stinging. We conclude that the parasitoid jewel wasp uses at least mechanosensory inputs from its stinger to identify the brain within the head capsule of the cockroach prey.